A student’s guide to Fourier transforms : - James, J. F. (Cambridge University Press, 2002)
This new edition of a successful textbook for undergraduate students in physics, computer science and electrical engineering describes important contemporary ideas in practical science and information technology at an understandable level, illustrated with worked examples and copious diagrams. The field is covered broadly rather than in depth, and includes references to more extended works on various topics. This new edition is slightly expanded, and includes additional new material in the applications sections.